2003
DOI: 10.1086/367706
|View full text |Cite
|
Sign up to set email alerts
|

Cell‐Associated Genital Tract Virus and Vertical Transmission of Human Immunodeficiency Virus Type 1 in Antiretroviral‐Experienced Women

Abstract: The precise mechanisms of vertical human immuno-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
47
1
4

Year Published

2004
2004
2009
2009

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(53 citation statements)
references
References 68 publications
1
47
1
4
Order By: Relevance
“…One recent study showed that breast milk HIV-1 DNA level, adjusted for breast milk HIV-1 RNA level, predicted HIV-1 vertical transmission in antiretroviral-naïve women (22). Similarly, HIV-1 DNA level, but not RNA level, in cervicovaginal secretions was an independent predictor of vertical transmission in treated women (25). These data suggest that cell-associated virus may play an important role in HIV-1 transmission.…”
mentioning
confidence: 96%
“…One recent study showed that breast milk HIV-1 DNA level, adjusted for breast milk HIV-1 RNA level, predicted HIV-1 vertical transmission in antiretroviral-naïve women (22). Similarly, HIV-1 DNA level, but not RNA level, in cervicovaginal secretions was an independent predictor of vertical transmission in treated women (25). These data suggest that cell-associated virus may play an important role in HIV-1 transmission.…”
mentioning
confidence: 96%
“…In the Kenyan study, vaginal and cervical swab samples were used and HIV-1 DNA was measured, whereas CVL samples were used in the present study and cell-free HIV-1 RNA was measured (Baeten et al, 2001). Both HIV-1 RNA and DNA levels in genital tract samples have been associated with HIV-1 MTCT, suggesting that both infected cells and cell-free virus may play a role in perinatal HIV-1 transmission (Montano et al, 2003;Tuomala et al, 2003).…”
Section: Discussionmentioning
confidence: 94%
“…Heterosexual transmission and mother-to-child transmission (MTCT) are the primary routes of infection for adults and children, respectively. Shedding of HIV-1 in the female genital tract (Montano et al, 2003;Tuomala et al, 2003) and levels of interleukin-1b (IL-1b) (Fichorova et al, 2001) are mediators of these routes of transmission, and identifying their determinants may help in the search of effective intervention strategies to lower HIV-1 transmission rates.…”
Section: Introductionmentioning
confidence: 99%
“…(2) Intrapartum durant le travail et l'accouchement [9]. Les sécré-tions vaginales contiennent du VIH sous forme de cellules infectées et de particules virales libres au contact desquelles l'enfant risque de s'infecter lors d'un accouchement vaginal [10], particulièrement par la voie oropharyngée [11]. (3) Postpartum dans le contexte de l'allaitement maternel [12].…”
Section: Mécanique De La Transmission Mère-enfant Du Vihunclassified